Wither The Asean Security Community? Some Reflections - Saravanamuttu, Johan (Penerbit Universiti Sains Malaysia (USM Press), 2005)
The paper argues that a security community remains an object rather than a reality among the Association of South East Asian Nations (ASEAN) countries. This notwithstanding, ASEAN institutions, processes and structures in the security regime have multiplied manifold over its 38 years of existence. Theoretical work on ASEAN suggests that a realist-institutional understanding of ASEAN should now be supplanted by what could be called "statecentric constructivism". However, the paper argues that such a theoretical development fails to fully account for the political construction of a security community based on some measure of civil society engagement albeit in the highly state-driven ASEAN formation. It is the understanding of this writer that the agency for change emanating from civil society forces still remains generally under-theorised.